King Bidgood's In The Bathtub - Wood, Audrey; Wood, Don, 1945- (San Diego : Harcourt Brace Jovanovich, 1985)
Despite pleas from his court, a fun-loving king refuses to get out of his bathtub to rule his kingdom.
new kids book 2024 summer.
Keywords: Kings, queens, rulers, etc. -- Fiction; Baths -- Fiction